A study of the reasons of students in their pursuit of the MLIS degree and their choice of MLIS school - Torres, Efren M., Jr (Institute of Library Science, University of the Philippines Diliman, 2002)
Having a master's degree is truly an advantage. Many people are starting to realize its importance for it really gives them security whether financially or morally. One of the numerous master's title is the Master of Library and Information Science which is considered as the only graduate degree level in the field of library and information science.